Evaluation of Glyceraldehyde 3-Phosphate Dehydrogenase (GADPH) and Luteinizing Hormone Receptor (LHR) Gene Polymorphisms in Buffaloes and Cows - Berdugo Gutiérrez, Jesús Alfredo; Pérez Arenas, Lina Marcela; Montoya-Ruiz, Carolina; Cardona Maya, Walter D. (Journal of Buffalo Science, 2025)
The present work evaluates whether buffalo and cattle have different sequences of luteinizing hormone receptor (LHr) and glyceraldehyde 3-phosphate dehydrogenase (GADPDH) genes. DNA was extracted from the peripheral blood of 38 animals (17 buffaloes and 21 cows) and the ovarian granulosa cells of 13 cows. Primers used for amplification were reported in the literature. The PCR products obtained were analyzed via electrophoresis on 1.5% agarose gels and sequenced via the Sanger technique. The electropherograms were analyzed via DNA Baser software, and the sequences were aligned via MEGA5 software. The quality of the electropherograms was evaluated via UGENE software.The edited contigs corresponding to the GAPDH gene were 100 nucleotides long, whereas those of the LHR gene reached 151 nucleotides. The most relevant changes were observed in the following positions: valine for isoleucine at position 65; asparagine for cysteine at position 67; alanine for glycine at position 70; threonine for proline at position 72; glycine for arginine at position 88; and alanine for aspartic acid at position 89. In the analyzed region, a variation was identified at position 446, where buffaloes preferentially present threonine, whereas in cows, alanine or valine.It is reported for the first time that there are differences in the LHr and GAPDH genes between buffaloes and cattle. The bioinformatic analysis of these sequences may explain whether the changes may affect the function of the genes and whether these may be responsible for the differences observed in the reproduction of the species analyzed.